Participatory mapping in community participation – case study of Jeseník, Czech Republic - Pánek, Jiří (Quaestiones Geographicae, 2018)
Community participation has entered the 21st century and the era of e-participation, e-government and e-planning. With the opportunity to use Public Participation Support Systems, Computer-Aided Web Interviews and crowdsourcing mapping platforms, citizens are equipped with the tools to have their voices heard. This paper presents a case study of the deployment of such an online mapping platform in Jeseník, Czech Republic. In total, 533 respondents took part in the online mapping survey, which included six spatial questions. Respondents marked 4,714 points and added 1,538 comments to these points. The main aim of the research was to find whether there were any significant differences in the answers from selected groups (age, gender, home location) of respondents. The results show largest differences in answers of various (below 20 and above 20 year) age groups. Nevertheless further statistical examination would be needed to confirm the visual comparison.